The Socialization and Training K3 at SMKN 3 Tegal City - Firmansyah, Hasbi; Weimintoro, Weimintoro; Salsabila, Nadya Shafira; H, Okky Hendra; Santoso, Teguh Haris; MD, M. Yusuf (ASEAN Journal of Empowering Community, 2023)
Indonesia's occupational safety and health (K3) has received special attention from the government. In general, the number of work accidents has decreased and increased, according to BPJS Employment data. Namely, in 2015 there were 110,285 work accident cases. In 2016 there was a decrease of 4.6 per cent, or there were 105,182 work accident cases, and in August 2017, there were 80,392 work accident cases. , in 2018 it rose to 173,415 cases. The number of work accident cases increased again in 2019 to 182,835 cases, and in 2020, work accident cases decreased slightly to 177,000. Based on this, the Universitas Pancasakti Tegal service team carried out community service activities by providing OSH training to SMK partners, aiming to equip SMK students with OSH knowledge from an early age. This community service program was carried out at SMK N 3 Tegal City for 11th-grade students with a total of 50 students. Community service activities use the concept of training. Apart from being given theoretical explanations, participants are also accompanied by examples of the application of OSH standards in the work environment which are shown visually as practices in handling hazards that threaten OSH. This training is expected to provide provisions to students carrying out work practices or apprenticeships in the industry. In general, the training activities offer knowledge and experience to vocational students to arouse their enthusiasm to apply them in the workplace later to achieve zero accidents.